Effect of Poverty on Political Participation in Dutse, Nigeria - Mackson Abga, Maina; Ndukwe Ikenga, Chinedu (Kashere Journal of Politics and International Relations, 2023)
The menace of poverty has devastating effect on democratic consolidation, as it result to electoral violence and, underdevelopment; this study aims to evaluate the effect of poverty on political participation in Nigeria with particular reference to Dutse local government area in Jigawa state, Survey research method was adopted and the data used in this study was collected from both primary and secondary sources. The primary source was through the use of questionnaire; while the secondary source was through the reading of relevant literature on the subject. The population of the study was Dutse local government area in Jigawa state; randomly, a total number of 100 samples were taken from the population, out of the 100 sampled respondents that were selected 78 were returned and used for analysis. The data collected were analyzed, using table and simple percentage for the data analysis; the findings of the study revealed that unemployment, corruption, poor environment, lack of capital, lack of health care services among others are the main causes of poverty and poverty served as mechanism for political thuggery, hijacking of ballot box among the other forms of political violence. The limitations the study encountered were inadequate time and financial constraints; more so, the study had problem in retrieving the questionnaire specifically for the primary data. The study recommends that the issue of poverty should be paid adequate attention by government at all levels in order to increase political participation and also reduce electoral violence in the local government and the country at large.